Analysis of the Level of Knowledge of Nurses Regarding Nutritional Diet Regimes - Abbas, Maimoona; Tasleem, Bushra; Nawaz, Farkhanda (Biological and Clinical Sciences Research Journal, 2025)
Nutritional counseling is a critical component of disease prevention and management. Nurses, being at the forefront of patient care, must possess adequate knowledge about dietary regimens to effectively guide patients with chronic diseases such as diabetes, cardiovascular disease (CVD), and obesity. However, data on nurses’ nutritional knowledge in hospitals remains limited in Pakistan. Objective: To analyze the knowledge of registered nurses regarding nutritional diet regimens for obesity, diabetes, and cardiovascular diseases (CVD) in a tertiary care hospital. Methods: A cross-sectional study was conducted in the Nursing Department of Nishtar Hospital, Multan, from February 2024 to February 2025. One hundred registered nurses working the day shift across various departments (internal medicine, neurology, surgery, obstetrics, pediatrics, and nephrology) were surveyed. Basic demographic data were recorded, including qualification, years of experience, and department. A validated 42-item questionnaire assessed knowledge of dietary management for diabetes, obesity, and CVD. Data were analyzed using SPSS version 25. Statistical significance was determined using appropriate inferential tests with a p-value ≤ 0.05. Results: The overall nutritional knowledge level among nurses was 59%, with subcategory scores of 69% for diabetes, 54% for obesity, and 59% for CVD. Knowledge scores were significantly higher among nurses with 11 or more years of experience (p = 0.019) and those holding a master’s degree (p = 0.018). However, knowledge scores across different hospital departments found no statistically significant difference. Conclusion: Nurses demonstrated below-average knowledge regarding nutritional regimens for patients with diabetes, CVD, and obesity. This highlights the urgent need for structured education and training programs focused on clinical nutrition to effectively empower nurses to manage the growing burden of non-communicable diseases.